Energy profile and improvement proposal of a sawdust charcoal briquette factory - Akmal Irfan Majid; Syafik Maulana; Willie Prasidha (Jurnal Penelitian Saintek, 2022)
This study aimed to analyze the proﬁle of energy consumption and identify eﬀorts to improve energy eﬃciency. In the present work, the evaluation was focused on the main production lines, including energy utilities sourced from electricity as well as an analysis of thermal energy-based equipment. A medium-scale charcoal plant in Yogyakarta was selected as the object of the present study to represent the characteristics of a sawdust charcoal briquette industry. Measurements of electrical current were made using a clamp meter to determine the utility of the electrical devices while an infrared thermal camera was used to determine the temperature distribution. Results of this study indicate that thermal energy has the largest proportion in the main production line. Some points of heat concentration were found which could potentially cause hazards and thermal discomfort. Ideas for improvement were also proposed qualitatively as a recommendation